ANALISIS PERKEMBANGAN PRODUKSI MINYAK MENTAH DAN GAS BUMI INDONESIA (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2012)
Upstream oil and gas industry of Indonesia have institutional changes in management responsibility upstream oil and gas industry in Indonesia. Deregulation of the upstream oil and gas industry aimed at institutional efficiency and optimization of oil and gas revenue for Indonesia. The study aims to track the progress of the development of oil and gas production and institutional role in the upstream industry in Indonesia. Data of this study is secondary data. The method of analysis of this study uses descriptive analytical method. The results showed that the development of Indonesia's oil and gas production inverses for the period 2000-2010. Indonesia's crude oil production declined each year during the period 2000-2010. Indonesia gas production tends to fluctuate during the period 2000-2010. Institutional changes have an impact on the growing amount of Contractors Cooperation Contract (K3S) production in Indonesia to be fluctuate.